HUBUNGAN KEBUGARAN JASMANI DENGAN INSOMNIA PADA MAHASISWA LAKI – LAKI TINGKAT AKHIR AKADEMIK FAKULTAS KEDOKTERAN UNIVERSITAS BATAM - Rini Susanti; Rusdani (Universitas Batam, 2023)
One of the factors that influence insomnia is physical fitness. The worse the physical fitness, the higher the risk of developing insomnia. Insomnia can have unwanted effects, so it needs good treatment. In this study aims to determine the relationship between physical fitness and insomnia in male final year students.This research method was analytic observational with a cross-sectional approach conducted at the Faculty of Medicine, University of Batam in 2016. The sampling technique was total sampling with a population of 49 people in 2016 which was determined by inclusion and exclusion criteria. Data analysis uses the Spearman Correlation test. Based on the results of this study, it was shown that of the 49 respondents, the majority had good physical fitness with 14 respondents (28.6%), those who experienced insomnia were in the non-insomnia category with 12 respondents (24.5%), mild insomnia with 11 respondents ( 22.4%), moderate insomnia with a total of 18 respondents (36.7), severe insomnia with a total of 8 respondents (16.3%). Pearson's correlation test obtained a significance of p <0.001 with a correlation coefficient (r) of (+) 0.801 . This figure shows that the value of r is at the significant level (r) = (+) 0.801 to + 1, meaning that there is a strong positive relationship between the two variables. This study concluded that there was a relationship between physical fitness and insomnia in male students at the end of the academic year at the Faculty of Medicine, University of Batam